1996
DOI: 10.1080/02786829608965360
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic Growth of Assorted Indoor Aerosols

Abstract: ABSTRACT. The hygroscopic growth of particles produced from four different kinds of oils during deep frying, from sausages during grilling, and from burning wood in a stove was studied using a Tandem DifferentialMobility Analyzer. The size distributions and the soluble fractions of the particles were also measured. The median diameters of the particles from the oils were in the range of 168-200 nm and those from the sausages and the wood in the range of 55-80 nm. The median diameter and the geometric standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 19 publications
(16 reference statements)
1
20
0
Order By: Relevance
“…In our study, we performed the cooking experiments by frying sausages with sunflower oil and toasting bread. This result is consistent with Dua and Hopke (1996), who observed that there was no growth of particles emitted from cooking oils and sweet Italian sausages.…”
Section: Resultssupporting
confidence: 92%
“…In our study, we performed the cooking experiments by frying sausages with sunflower oil and toasting bread. This result is consistent with Dua and Hopke (1996), who observed that there was no growth of particles emitted from cooking oils and sweet Italian sausages.…”
Section: Resultssupporting
confidence: 92%
“…The fuels used in that study were, however, not typical for the Amazon region. Dua and Hopke (1996) showed that the aerosol particles from flaming fires (burned in a non-optimized way) were hydrophobic (soot) while particles from the smoldering phase (non-combusted organic compounds) had a hygroscopic growth factor of around ∼2, measured at 99% RH (corresponding to a Gf ∼1.35 at 90% RH). To summarize, in this study both freshly emitted and aged aerosol particles originating from biomass burning smoke had quite low hygroscopic growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Weingartner et al (1997) showed that freshly produced diesel particles have very low hygroscopic growth factors close to 1.0 when exposed to a RH up to 99%. Dua and Hopke (1996) showed that particles from a residential wood stove with flames burning had growth factors close to 1.0 at RH~99%. However, during smouldering growth factors of around 2.0 were reported.…”
Section: Introductionmentioning
confidence: 99%